The effect of team formation on match running performance in UEFA Champions League matches: implications for position-specific conditioning - Modric, T.; Versic, S.; Winter, C.; Coll, I.; Chmura, P.; Andrejewski, M.; Konefal, M.; Sekulic, D. (Science and Medicine in Football, 2023)
This study aimed to determine the effect of team formation on position-specific match running performance (MRP) at highest-level football. Players` MRP (n = 226) was observed in four team formations: 3-5-2 (n = 24), 4-4-2 (n = 44), 4-2-3-1 (n = 77) and 4-3-3 (n = 81). Central defenders in the 3-5-2 formation achieved a greater amount of high-intensity running distance than in the 4-3-3 formation (mean difference (MD) [95% confidence interval] = 144 m [12, 267], medium ES). Fullbacks in the 4-4-2 formation covered less total distance than in 3-5-2 (MD = -762 m [-1431, -94], large ES) and 4-2-3-1 (MD = -662 m [-1055, -269], medium ES). Central midfielders` total distance in the 4-4-2 formation was lower than that in the 3-5-2 (MD = -645 m [-79, -1211], medium ES) and 4-3-3 (MD = -656 m [-1181, -132], medium ES) formations. Wide midfielders` walking distance in the 4-4-2 formation was lower than that in the 4-3-3 (MD = -484 m [-742, -226], very large ES) and 4-2-3-1 (MD = -535 m [-789, -282], very large ES) formations. Forwards` high-intensity running in the 4-2-3-1 formation was lower than that in the 4-3-3 (MD = -363 m [-613, -112], large ES) and 4-4-2 (MD = -396 m, [-688, -103], large ES) formations. These findings show that conditioning programs for players on all playing positions should be tailored according to the formations of their teams.